Capital Structure and Firm's Growth in Relations to Firm Value at Oil and Gas Companies Listed in Indonesia Stock Exchange - Muhammad Daffa Hamam; Layyinaturrobaniyah Layyinaturrobaniyah; Aldrin Herwany (Journal of Accounting Auditing and Business, 2020)
The value of the firm is an investor's perception of the firm's success that is often associated with the performance of its shares. The height of the firm’s value, indicating that the market believes in not only the firm's present condition but also in the firm's prospect. Several factors are thought to affect the value of the firm, like funding decisions, dividend policy, stock decision, firm growth, and firm size. This study aims to see whether there is any effect of capital structure and the level of firm growth on firm value. The sample used in this study was six oil and gas companies listed on the Indonesia stock exchange in the 2013-2017 period. Regression analysis is built on an unbalanced panel data set. The results of this study indicate that the capital structure proxied by the variable debt to equity ratio has a negative coefficient direction but is not significant to the firm's value, while the growth rate has a positive effect coefficient direction on the firm's value but also not significant